FTIR spectroscopy analysis of Halal and non-Halal gelatin as raw material derived from animal bones - Mohd Sopian, Hanisah; Mirghani, Mohamed Elwathig Saeed; Marikkar, Mohammed Nazrim; Hammed, Ademola Monsur (2017)
Halal gelatin is a global demand for Muslims in both food and nonfood industries. Unfortunately, the greater portion of the world supply of gelatin is usually derived from non-halal animals. While the production of gelatin replacements has existed for many years for the vegetarian, halal and kosher markets, the issue regarding the halal status of mammalian bone-derived gelatins is still ongoing. Availability of methods to distinguish bone gelatins of swine from those of other animal sources such as cow and goat is also scanty. This study aims to utilize the Fourier transform infrared (FTIR) spectroscopy as one of the analytical methodologies that can help to identify the source of origin of bones. In this study, bones from various types of animals such as cow, goat, and pig were characterized and used as raw materials for gelatin production introducing new protocols and interdisciplinary spectroscopic instrumental techniques. Bones were also, prepared (pre-treatment) for processing and production / extraction of gelatin and the extraction of crude gelatin using various methods. Amide bands of the different gelatins as observed from the spectra were associated with respective functional groups. The results showed that FTIR spectroscopy is a rapid reliable technique to differentiate bones from various animals as well as the crude gelatin produced from different animals’ bones.